Gastrocnemius Strain: A Case Study - Rizvi, Arif; Asthana, Sumit; Dwivedi, Anuj; Fatima, Tahzeeb; Khan, Wahida; Raheed, Rutba (Journal of Biomedical and Pharmaceutical Research, 2024)
Gastrocnemius Strain is a painful condition of partial tearing of the medial belly of the gastrocnemius, caused by overstretching the muscle by concomitant ankle dorsiflexion and full knee extension. Contributory factors are muscle fatigue and degenerative changes [1]. The purpose of the case study is to present a case of Gastrocnemius Strain, who underwent physiotherapy department. The 35 years male was having pain in the left calf muscle for last eight days. According to the patient the pain started while running in the field for practicing for an upcoming sports event. He felt sudden acute pain in the left leg, followed by swelling after he placed his left heel on the field. He went to consult a physiatrist in a private hospital nearby. During examination, in clinic there was swelling, tenderness around the middle & lower part of left Gastrocnemius muscle. There was increase pain in the leg during dorsiflexion of left foot, both active & passive. He was unable bear full weight on the affected limb. Measurement of right & left Gastrocnemius muscle was 38 cm & 40 cm respectively, from 8 cm below tip of patella. The Thompson squeeze test was negative though it was painful. He was walking in non-weight bearing pattern using walker. M.R.I report suggested, there was fluid collection in left calf muscle, between Soleus & medial head of Gastrocnemius, most prominent at the myotendinous junction. There was also tear with oedema in anterior fibres of left mid & distal part of lateral head of Gastrocnemius & anterior fibres of distal part of medial head of Gastrocnemius. The patient was treated with low-level laser therapy for 15 sittings & was advised to apply Cryotherapy followed by crepe bandage application. After completion of treatment, there was minimum tenderness or pain in the affected area. The patient was able to bear full weight on the left limb. He was advised to continue exercises for strengthening Gastrocnemius & Soleus muscle at home as demonstrated. Pain was measured using V.A.S on the first day before & last day after treatment. Keywords: Gastrocnemius Strain, low-level laser therapy, clinical case, calf muscle injury, Cryotherapy..